Participatory water management at the main canal: a case from South Ferghana canal in Uzbekistan - Abdullaev, Iskandar; Kazbekov, Jusipbek S.; Manthrithilake, Herath; Jumaboev, Kahramon (2009)
After the independence of Central Asian countries, many international projects have been launched to promote water users' inclusion into the water management at different levels. The aim of such projects is to achieve sustainable water management through inclusion of interests of different groups on day-to-day water management. Although IWRM in Central Asia has been already promoted for a decade, there are only a few examples of the implementation in real life situations. The Integrated Water Resources Management in Ferghana Valley (IWRM FV) is a pilot project on implementing integrated water resources management elements at the main canal levels and below. The experience gained from IWRM FV project and lessons learnt could be useful for the national and international organizations for their future work on IWRM implementation at the different regions of Central Asia. IWRM FV project has been active since 2001 in the Ferghana Valley, one of the largest irrigated areas of Central Asia. The project has promoted and implemented participatory irrigation management for three pilot canals. This paper presents the process of implementation and some preliminary outcomes of the IWRM VF project.